Biocolmation and the finite element modeling of its influence on changes in the head drop in a geobarrier - Ulyanchuk-Martyniuk, Oksana; Michuta, Olga; Ivanchuk, Natalia (Eastern-European Journal of Enterprise Technologies, 2020)
The influence of the biocolmation of the geobarrier for organic waste storage on the values of head drops has been investigated. A mathematical model of filtration of organic substances taking into consideration the biocolmation effect was formed. The mathematical model contains the equation of filtration under conditions of variable porosity. In addition, the mathematical model includes the equation of transfer of organic chemical substances in pore fluid and the equation of dynamics in bacteria biomass in a porous medium based on the Monod equation. The problem in the region with a thin inclusion was solved by the method of finite elements. The schematic algorithm of finding an approximate solution of the boundary problem, including the scheme of discretization over time, is presented. Numerical experiments were conducted with an analysis of their results. In particular, the tables have been given of the values of heads and their drops on inclusions when biocolmation is neglected and the values of heads and their drops on inclusions while taking into account biocolmation at specific moments of time. The numerical experiments showed that the existence of microorganisms in soil pores significantly influences the values of heads at the top and at the bottom of a geobarrier. In particular, relative changes in head drops, in comparison with the case of disregarding the influence of microorganisms, can reach 54.8 % towards an increase. Such differences, in turn, lead to a change in the estimation calculations of the propagation of waste storage contamination into groundwater. They can also cause negative changes in the stressed-strained state of a soil array in the vicinity of a geobarrier as a type of a thin inclusion and lead to the intensification of shear processes. At the same time, due to the nonlinearity of influences and complex interdependence among processes, it is not possible to predict such values and their differences without computer simulation and mathematical modeling